UPON THE PREVALENCE OF ENGLISH ON BILLBOARD ADVERTISEMENTS: ANALYZING THE ROLE OF ENGLISH IN INDONESIAN CONTEXTS - Anna Marietta da Silva (TEFLIN, 2014)
Â Looking at the frequently used English words on billboard ads in Jakarta main streets, one may have a presumptive thought that English will dominate Indonesian language. The assumption, though, has led to the analysis of the role of both languages on billboard ads and the possibility of English control over Indonesian. The study presented purposive language uses. English, regardless of its incorrect use, was associated with the Indonesian modern, urban and youthâs lifestyle, hence the prestigious status of English. On the other hand, Indonesian and its dialects, particularly the Betawi-Indonesian, are employed to cover wider and broader range of audience. Indonesian language is a national identity of Indonesians, and has historically gained highest status among hundreds of local languages in Indonesia. Thus, in spite of the presence of English in Indonesian language use, the former will not diminish the latter. As a matter of fact, the two languages serve different types of readers.Â